Morphology of the Vasculature and Blood Supply of the Brown Adipose Tissue Examined in an Animal Model by Micro-CT - Mrzilkova, J; Michenka, P; Seremeta, M; Kremen, J; Dudak, J; Zemlicka, J; Musil, Vladimír; Minnich, B; Zach, P (BioMed research international, 2020)
We performed micro-CT imaging of the vascular blood supply in the interscapular area of the brown adipose tissue in three mice with the use of intravascular contrast agent Aurovist™. Resulting 3D data rendering was then adapted into 2D resolution with visualization using false color system and grayscale images. These were then studied for the automatic quantification of the blood vessel density within this area. We found the highest most occurring density within arterioles or venules representing smaller blood vessels whereas with the increase of the vessel diameters a lower percentage rate of their presence was observed in the sample. Our study shows that micro-CT scanning in combination with Aurovist™ contrast is suitable for anatomical studies of interscapular area of brown adipose tissue blood vessel supply.
Keywords: Animals; Blood Vessels; Venules; Adipose Tissue, Brown; hnědá tuková tkáň; zvířata; cévy; rentgenová mikrotomografie; Mice; Mice, Inbred C57BL; X-Ray Microtomography; zobrazování trojrozměrné; venuly; Imaging, Three-Dimensional; myši inbrední C57BL; myši